The Final Frontier : America, Science, and Terror - Jenkins, Dominick (London Verso, 2002)
In this original work Dominick Jenkins provides a meticulously researched history of the First World War origins of the current relationship between the American presidency and US weapons laboratories." "The comparisons Jenkins draws with the contemporary situation are clear and compelling: As with the German sinking of the Lusitania in 1915, the 11 September attacks are now being used to convince Americans to back the expansion of presidential power and a permanent war against rogue states and terrorists." "Engaging with theorists such as Foucault, Lyotard and Agamben, The Final Frontier crosses the boundaries between history, ethics, law, politics, and science, developing a powerful and highly topical argument through the use of vivid historical examples. It will be of interest not only to specialists but to anyone interested in the history of science, technology, and the military, as well as providing compelling reading for activists in the peace, environmental, and anti-globalization movements."--Jacket.
Include Notes and Index
Keywords: Military policy -- Military-industrial complex -- Science and state